The Enduring Problem of Statism: Social War, Total Liberation and Postdevelopment in the Decolonization Industry - Dunlap, Alexander (Development and change, 2025)
Confronting statism within the university, this article argues that statism is colonialism. By recognizing statism as the foundational structure of colonialism, the author illuminates the immediate technologies and evolving structures of socio‐ecological subjugation across various cultural, historical and political contexts. This lens locates the political roots, and reproduction, of coloniality, identifying the state as an environmental shaping infrastructure and psycho‐political technology that penetrates the bodies and minds of people. Rooted in postdevelopment and anarchist thought, the article reviews definitions of imperialism, (settler‐)colonialism and genocide/ecocide. The main section discusses how statism is colonialism, locating the general structures and impacts, and recognizing the ‘modernized poverty’ often hidden by (uneven) affluence. This leads to a discussion of statism(s) in relation to pluriversal politics and the struggle ahead for postdevelopment thought.